Simulator training in focus assessed transthoracic echocardiography (FATE) for undergraduate medical students: results from the FateSim randomized controlled trial - Johannes Matthias Weimer; Franziska Marietta Sprengart; Thomas Vieth; Sebastian Göbel; Anna Dionysopoulou; Rebecca Krüger; Jan Beer; Andreas Michael Weimer; Holger Buggenhagen; Roman Kloeckner; Lukas Pillong; Johanna Helfrich; et al. (BMC Medical Education)
Abstract Introduction Ultrasound is important in heart diagnostics, yet implementing effective cardiac ultrasound requires training. While current strategies incorporate digital learning and ultrasound simulators, the effectiveness of these simulators for learning remains uncertain. This study evaluates the effectiveness of simulator-based versus human-based training in Focused Assessed with Transthoracic Echocardiography (FATE). Materials and methods This single-centre, prospective, randomised controlled study was conducted during an extracurricular FATE workshop (approximately 420 min) for third-year medical students. Participants were randomly assigned to the study group (training solely on simulators) or the control group (training on human subjects). Both groups completed a theory test and a self-assessment questionnaire before the course (T1) and at the end of the training (T2). At T2, all participants also completed two Direct Observation of Procedural Skills (DOPS) tests—one on the simulator (DOPSSim) and one on humans (DOPSHuman). Results Data from 128 participants were analysed (n = 63 study group; n = 65 control group). Both groups exhibited increased competency between the T1 and T2 self-assessments and theory tests (p < 0.01). In the DOPSHuman assessment at T2, the control group performed significantly better (p < 0.001) than the study group. While motivation remained consistently high among both groups, the study group rated their “personal overall learning experience” and the “realistic nature of the training” significantly worse than the control group (p < 0.0001). Both groups supported the use of ultrasound simulators as a “supplement to human training” (study: 1.6 ± 1.1 vs. control: 1.7 ± 1.2; p = 0.38), but not as a “replacement for human training” (study: 5.0 ± 2.3 vs. control: 5.4 ± 2.1; p = 0.37). Conclusion Both simulator- and human-based training effectively developed theoretical and practical skills in FATE. However, the simulator group demonstrated significantly poorer performance when applying their skills to human subjects, indicating limitations in the transferability of this simulator-based training to real-life patient care. These limitations of simulator-based ultrasound training should be considered in future training concepts. Clinical trial number Not Applicable.